Penentuan Kadar Beberapa Mineral dan Keasaman Serta Uji Bakteriologi dari Beberapa Air Minum Isi Ulang di Siteba Kota Padang - Krisyanella Krisyanella; Yesi Nofrisari; Roslinda Rasyid (Jurnal Farmasi Higea, 2010)
The quantitation of some minerals such as iron, zinc, magnese, acidity measurament and bacteriological analysis from same refilling water samples which are collected in Siteba, Padang has been done. Mineral measurement was done by Atomic Absorption Spectroscopy (AAS). Acidy measurement done by acidy meter, and it’s bacteriological analysis done by using MPN (Most Probable Number) method. The result showed iron quantity from sample A, B, and C are 0,0615 mg/L; 0,0745 mg/L; 0,0747 mg/L respectively. It’szink quantity are 0.0110 mg/L; 0.0078 mg/L; 0.0110 mg/L respectively. Its magnese quantity is 0.0228 mg/L; 0 mg/L; 0 mg/L respectively. It’s acidy levels are 6.50; 6.61; 7.00. Its bacteriological number (Escherichia coli) is 5/100 mL; 0/100 mL; 96/100 mL. It showed that sample A and C have not complied the water qualification of public health RI. No. 907/MENKES/SK/VII/2002 in bactriological compounds.